2021
DOI: 10.1177/0047287520987624
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Authenticity, Well-being, and Memorability in Heritage Tourism: A Two-Site Investigation

Abstract: Authenticity, well-being, and memorability are essential to understanding tourist experience, yet little is known about the mechanism underlying these interrelated concepts. This study explores how tourists’ perceived authenticity influences memorability through their existential authenticity and well-being in the context of heritage tourism. Using data from visitors to two world heritage sites in China (West Lake and Lijiang), the effects of existential authenticity on tourists’ psychological and subjective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 61 publications
(205 reference statements)
3
35
1
Order By: Relevance
“…Constructive authenticity did not have a significant effect on memorability or organizational identification, which differs from the findings of studies related to heritage tourism (Lee et al , 2015; Yi et al , 2022). Wellness tourism emphasizes a harmonious interactive experience that aligns tourists’ body, mind and spirit with the objective environment to help them achieve wellness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Constructive authenticity did not have a significant effect on memorability or organizational identification, which differs from the findings of studies related to heritage tourism (Lee et al , 2015; Yi et al , 2022). Wellness tourism emphasizes a harmonious interactive experience that aligns tourists’ body, mind and spirit with the objective environment to help them achieve wellness.…”
Section: Discussioncontrasting
confidence: 99%
“…Participating in such activities is essential for creating memorable tourism experience (Pine and Gilmore, 1999). This result echoes with studies on tourism with specific interests such as heritage tourism (Yi et al , 2022) or in specific environments such as hotels (Mody et al , 2019). In addition, the pursuit of wellness motivates tourists to stay in spa hotels.…”
Section: Discussionsupporting
confidence: 74%
“…Other studies have suggested that authenticity affects RI via PA (Shang et al, 2020 ; Yi et al, 2021b ). Drawing on the CAT theory, we found that both MTEs and PA play an independent mediating role successively between authenticity and RI, which is consistent with previous studies (Shang et al, 2020 ; Rasoolimanesh et al, 2021 ; Yi et al, 2021a ). In addition, MTEs and PA played a multiple-step mediating role in the relationship between authenticity and RI.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Cao et al ( 2019 ) reported that social relationships improve tourists' memory of travel experiences in the restaurant environment. Yi et al ( 2021a , b ) also confirmed that EA affects unforgettable experiences in heritage tourism. In addition, research has indicated that tourism based on authentic objects and sincere interactions leads to positive memorable experiences (Domínguez-Quintero et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 82%
“…The implicit promotion of existential authenticity can be attributed to the advantageous nature of tourism that activates the individual desire for self-exploration and self-connection with constant exposure to novel activities, places, peoples, or cultures (Yi et al 2021). The novel exposures (even for a limited level) urge the updated understanding of self-identity in relation to the external world (Matteucci and Filep 2017; Schultz and Tabanico 2007).…”
Section: Literature Reviewmentioning
confidence: 99%